Reliability, maintainability and risk : practical methods for engineers - Smith, David J. (David John), 1943 June 22- (Elsevier Butterworth-Heinemann, 2005)
For over 30 years, Reliability, Maintainability and Risk has been recognised as a leading text for reliability and maintenance professionals. Now in its seventh edition, the book has been updated to remain the first choice for professional engineers and students. The seventh edition incorporates new material on important topics including software failure, the latest safety legislation and standards, product liability, integrity of safety-related systems, as well as delivering an up-to-date review of the latest approaches to reliability modelling, including cutsec ranking. It is also supported by new detailed case studies on reliability and risk in practice.